2016
DOI: 10.1038/srep33222
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and Repair Modify DNA methylation and Chromatin Domain of the Targeted Locus: Mechanism of allele methylation polymorphism

Abstract: We characterize the changes in chromatin structure, DNA methylation and transcription during and after homologous DNA repair (HR). We find that HR modifies the DNA methylation pattern of the repaired segment. HR also alters local histone H3 methylation as well chromatin structure by inducing DNA-chromatin loops connecting the 5′ and 3′ ends of the repaired gene. During a two-week period after repair, transcription-associated demethylation promoted by Base Excision Repair enzymes further modifies methylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 35 publications
2
59
0
Order By: Relevance
“…As DNA damage has been proposed as a mechanism for DNA methylation changes (Russo et al, 2016), we assessed DNA damage in the samples analyzed in the current study. We used the alkaline comet assay to measure sperm DNA damage and, as reported previously, we found marginally increased DNA damage in sperm from men who smoke compared with controls (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…As DNA damage has been proposed as a mechanism for DNA methylation changes (Russo et al, 2016), we assessed DNA damage in the samples analyzed in the current study. We used the alkaline comet assay to measure sperm DNA damage and, as reported previously, we found marginally increased DNA damage in sperm from men who smoke compared with controls (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the localization and density of the methylation sites in each cell clone, the expression of the repaired gene progressively changes [11][12][13][14]. Thus, methylated clones will dominate over others if silencing of the gene produces a strong positive selection.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing possibility lies in the targeted DSB induction. Studies in mammalian cells have shown that targeted DNA methylation occurs upon homology-mediated repair of induced DSBs, resulting in variable gene expression among cells (Cuozzo et al, 2007;Morano et al, 2014;Russo et al, 2016). This is facilitated through recruitment of DNA methyltransferases and histone-modifying enzymes at the DSB during HR.…”
Section: Discussionmentioning
confidence: 99%